2020
DOI: 10.1021/acsami.0c00552
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectricity and Biocompatibility of Flexible ScxAl(1–x)N Thin Films for Compliant MEMS Transducers

Abstract: There is huge research activity in the development of flexible and biocompatible piezoelectric materials for next-generation compliant micro electro-mechanical systems (MEMS) transducers to be exploited in wearable devices and implants. This work reports for the first time on the development of flexible Sc x Al(1–x)N films deposited by sputtering technique onto polyimide substrates, assessing their piezoelectricity and biocompatibility. Flexible Sc x Al(1–x)N films have been analyzed in terms of morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Luciana Algieri et al in his article reported different techniques inorder to understand and verify the influence of doped flexible ScxAl(1-x) N films. They analysed surface morphology performance by atomic force microscopy, structural properties by scanning electron microscopy, diffraction pattern analysis by X-Ray Diffractometry, scandium concentration analysis by X-ray Energy Dispersive Spectroscopy, piezo electric property analysis by Piezo response Force microscopy, Bending/unbending measurements by linear micro-actuator and control board managed by ARDUINO, voltage measurement by oscilloscope and finally cyclotoxicity determination by Cell viability assay (22).In 2021 Kristina Bespalova et al investigated the effect of Sc in Scandium-alloyed aluminum nitride (AlScN). They prepared sample by sputter deposition, morphology analysis by scanning electron microscopy, analysis of formation of new phase-X-ray diffraction (XRD) analysis, crystal quality analysis by Diffractogram indexing, X-ray rocking curves (XRCs) were measured, Electron-transparent lamellas were prepared using Focused Ion Beam Scanning Electron Microscopy(SEM), selected area electron diffraction (SAED), and energy-dispersive X-ray spectroscopy (EDX) mapping were used to acquire more accurate information on the metal/piezoelectric interface (23).…”
Section: Ecs Transactions 107 (1) 15229-15237 (2022)mentioning
confidence: 99%
“…Luciana Algieri et al in his article reported different techniques inorder to understand and verify the influence of doped flexible ScxAl(1-x) N films. They analysed surface morphology performance by atomic force microscopy, structural properties by scanning electron microscopy, diffraction pattern analysis by X-Ray Diffractometry, scandium concentration analysis by X-ray Energy Dispersive Spectroscopy, piezo electric property analysis by Piezo response Force microscopy, Bending/unbending measurements by linear micro-actuator and control board managed by ARDUINO, voltage measurement by oscilloscope and finally cyclotoxicity determination by Cell viability assay (22).In 2021 Kristina Bespalova et al investigated the effect of Sc in Scandium-alloyed aluminum nitride (AlScN). They prepared sample by sputter deposition, morphology analysis by scanning electron microscopy, analysis of formation of new phase-X-ray diffraction (XRD) analysis, crystal quality analysis by Diffractogram indexing, X-ray rocking curves (XRCs) were measured, Electron-transparent lamellas were prepared using Focused Ion Beam Scanning Electron Microscopy(SEM), selected area electron diffraction (SAED), and energy-dispersive X-ray spectroscopy (EDX) mapping were used to acquire more accurate information on the metal/piezoelectric interface (23).…”
Section: Ecs Transactions 107 (1) 15229-15237 (2022)mentioning
confidence: 99%
“…physical and physiological signs) and in-situ disease treatment [258][259][260]. Furthermore, with the unique capability for energy harvesting, piezoelectric devices can obtain more diverse functionalities in wearable and implantable applications, such as energy harvesting, self-powered monitoring, and self-powered stimulation [261][262][263][264][265][266][267][268][269][270][271]. Therefore, in this section, the recent developments of piezoelectric devices toward wearable and implantable applications are discussed.…”
Section: Development and Application Trends Of Piezoelectric Mems In ...mentioning
confidence: 99%
“…They need compact devices or a small footprint for particular operations [1][2][3][4]. Their high integrative power [5,6], low heat [7,8], and low noise levels [9,10] can provide relatively large efforts, high reliability, and biocompatibility [11][12][13][14]. Because of these benefits, the piezoelectric actuator has been widely used in a variety of industries, including space exploration [15,16], active shutters, pulsed jets [17][18][19], vibration control [20][21][22][23][24], optical path control [25][26][27][28], micro-motorization of instruments [29,30], valves and pumps for implants [31][32][33][34][35][36], magnetic resonance imaging (MRI) [37,38], microsurgery [39][40][41][42], and other micro-displacement techniques [43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%